Desenvolvimento sustentável como balizador da atividade empresarial no uso da logística reversa - Gimenes, Tatiana de Cassia (2020)
This work aims to study sustainable development in business activity and its social responsibility in the use of reverse logistics. Protection of the environment becomes a mandatory measure in business activity, as an integral element of sustainable development, not only to realize human needs, guarantee profitability, but also to serve as an instrument for improving the quality of life and well-being. to be social. The mass society has radically altered the scale of production of goods necessary for social coexistence, expanding the exploitation of natural resources and, consequently, generating intense impacts. It cannot be overlooked that business economic activity is responsible for a large part of this degradation, so that its conservation, as an economic agent that uses raw materials, is also threatened, coupled with the fact that its activity still puts the healthy quality of life at risk. present and future. To this end, the environmental principles and guarantees enshrined in current legislation are carefully examined, from the point of view of the content of the right to an ecologically balanced environment in all its extension and scope, whether the natural, artificial, cultural or work environment. It also examines the environment and sustainable development, as well as its challenges and the social focus as a compromise of balance between man and the environment. The method used is the hypothetical-deductive.